Editorial [Hot Topic: Appetite (Guest Editor: Willis K. Samson)] - Samson, Willis K. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
The National Institutes of Health (U.S.A.) identifies several major causes/risk factors as essential contributors to the global epidemic of obesity. These include dysregulated energy balance (more energy intake than energy output), genes and family history, environment, health conditions, medicines, emotional factors, aging, and lack of sleep. [1]. One risk factor that can be controlled is energy balance. This requires leveling of the “teeter-totter” of fuel supply and fuel expenditure. Physical inactivity, as a result of a sedentary lifestyle or the consequence of another illness, is a major contributor to the imbalance, resulting in a shift toward overweight and obesity. Additional contributors are altered utilization of fuel supplies as occurs in metabolic disorders such as Diabetes. Even under those circumstances, weight gain requires fuel intake that exceeds its eventual utilization. Here is where the study of Appetite takes center stage in the battle against the obesity. The promise of pharmacologic manipulation of appetite in healthy individuals and, importantly, in patients with metabolic disorders, has driven the study of the central nervous system regulation of feeding. Not surprisingly, factors discovered to influence hunger/satiety by central nervous systems actions also play important roles in the peripheral utilization of dietary fuel supplies. In this Special Issue, an attempt was made not to comprehensively detail the literature on Appetite, but instead to provide several key examples of how the studies of fuel intake and fuel utilization have converged. This is in large part due to the realization that peptide hormones of both peripheral and central nervous system (CNS) origin significantly affect both sides of the “teeter-totter.” The Issue begins with a review of how factors that affect Appetite exert their actions within the CNS. In that review, Ferguson and Sharkey (Kingston and Calgary, Canada) identify the five potential mechanisms by which satiety factors can reach those centers, highlighting the importance of signals arriving via the afferent limb of the Vagus nerve and blood brain barrier free sites in CNS, known as sensory circumventricular organs (CVOs). Gibson and Korbonits (London, United Kingdom) then describe the multiple neuropeptides reported to affect food intake and appetite regulation and detail the intriguing concept of competing and potentially opposing hormones derived from the same gene product, ghrelin and obestatin. Here the concept of post translational modification of products of the same gene identifies a novel approach to the understanding of appetite regulation and possible modification. Can those post translational modifications be therapeutic targets, in this case to octanoylation of ghrelin by the recently described enzyme, ghrelin 0-acyltransferase (GOAT)? Already pharmacologic tools capable of modifying the activity of this enzyme are available for testing in experimental models. The importance of aminergic signaling in CNS to appetite regulation has been recognized for decades and selective agonists and antagonists have been developed for the study of satiety. This has led to novel classes of drugs including selective serotonin (5-hydroxytryptamine, 5-HT) reuptake inhibitors (SSRIs) and 5-HT/noradrenalin reuptake inhibitors (SNRIs) that hold promise as appetite suppressants. In the review by Nonogaki (Sendai, Japan), the promise as well as the complications of clinical use of these potent compounds is detailed, providing insight into the difficulty of targeting CNS appetite regulation in isolation, without secondary consequences. The Special Issue concludes with two reviews that detail the convergence of appetite regulation and glucose utilization. Bello and Moran (Baltimore, USA) detail the actions of glucagon-like peptide-1 (GLP-1) to stimulate insulin secretion and participate in the regulation of gastric emptying. Acting as the “ileal brake,” GLP-1 contributes to the CNS regulation of food intake by providing via the Vagus nerve, the afferent signal of satiety (i.e. fullness). In addition this hormone is produced in brain, where it interacts with known feeding pathways to suppress appetite. Potential therapeutics have been developed that either prolong the half life of GLP-1 by inactivating the enzymes that process the peptides, or by developing enzyme resistant peptide analogs. Some of these have been approved by the FDA for clinical use as adjunctive therapy in non-insulin dependent diabetes mellitus (NIDDM). Development of these analogs relied upon the knowledge of the mechanisms, detailed in the Ferguson and Sharkey review, of how agents administered peripherally might access CNS satiety centers. The Special Issue concludes with a comprehensive description by Parkes and colleagues (San Diego, USA) of how pharmaceuticals are developed to treat glucose metabolism and body weight regulation. The authors chronicle the development of amylin analogs as therapies for diabetes and weight management. This review highlights the importance of combinatorial chemistry and the availability of appropriate animal models to the development of effective therapeutic candidates.